PENGARUH EARNING MANAGEMENT, CORPORATE SOCIAL RESPONSIBILITY, KEBIJAKAN HUTANG DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH PRAKTEK GOOD CORPORATE GOVERNANCE - Andry Firmansyah, 10.05.52.0072; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2014)
This study aimed to analyze the effect of earnings management, corporate social responsibility the value of corporate debt policy are moderated by the practice of good corporate governance with the perspective of agency theory and signaling theory. This study used a sample of 53 publicly traded companies listed on at the Indonesian Institute of Corporate Governance in the form of corporate Governace perception index (CGPI) year period from 2010 to 2012. Hypothesis testing is used multiple regression analysis with absolute value of the difference. Results of studies using regression proved that earnings management, corporate social responbility and financial performance not affect the value of the company, debt policy affect the value company , good corporate governance is not proven as a moderating variable between earnings management, debt policy and financial performance with corporate values, good corporate governance proved to be moderating variable between CSR with corporate values.Keywords: Earning Management, Corporate Social Responsibility, Debt Policy, financial performance, Corporate Value, Good Corporate Governance